Neuroglial Involvement in Abnormal Glutamate Transport in the Cochlear Nuclei of the Igf1−/− Mouse - Fuentes-Santamaría, Veronica; Alvarado, Juan C.; Rodríguez-de la Rosa, Lourdes; Juiz, José M.; Varela-Nieto, Isabel (Frontiers in Cellular Neuroscience, 2019)
Insulin-like growth factor 1 (IGF-1) is a powerful regulator of synaptic activity and a deficit in this protein has a profound impact on neurotransmission, mostly on excitatory synapses in both the developing and mature auditory system. Adult Igf1-/- mice are animal models for the study of human syndromic deafness; they show altered cochlear projection patterns into abnormally developed auditory neurons along with impaired glutamate uptake in the cochlear nuclei, phenomena that probably reflect disruptions in neuronal circuits. To determine the cellular mechanisms that might be involved in regulating excitatory synaptic plasticity in four-month-old Igf1-/- mice, modifications to neuroglia, astroglial glutamate transporters and metabotropic glutamate receptors (mGluRs) were assessed in the cochlear nuclei. The Igf1-/- mice show significant decreases in IBA1 (an ionized calcium-binding adapter) and GFAP (glial fibrillary acidic protein) mRNA expression and protein accumulation, as well as dampened mGluR expression in conjunction with enhanced glutamate transporter 1 (GLT1) expression. By contrast, no differences were observed in the expression of glutamate aspartate transporter (GLAST) between these Igf1-/- mice and their heterozygous or wildtype littermates. These observations suggest that congenital IGF-1 deficiency may lead to alterations in microglia and astrocytes, an upregulation of GLT1, and the downregulation of groups I, II and III mGluRs. Understanding the molecular, biochemical and morphological mechanisms underlying neuronal plasticity in a mouse model of hearing deficits will give us insight into new therapeutic strategies that could help to maintain or even improve residual hearing when human deafness is related to IGF-1 deficiency.